PWE-125 Managing The Malignant Polyp: Surveillance or Surgery?. (17th August 2016) - Cargill, Z; Masding, A; Raju, R; Mann, S
Abstract : Introduction: A 'malignant polyp' contains cancer cells that have breached the mucosa. Usually this refers to a polyp that is resected endoscopically and appears benign, but contains carcinoma on histological analysis. A reported 0.75–5.6% of polyps removed at colonoscopy are malignant. 1 However practice is varied regarding subsequent management. Options include colonoscopic surveillance or surgery, utilising criteria to estimate the risk of cancer spread following polypectomy versus the risk of surgery. Methods: Patients were identified from the colorectal cancer multidisciplinary team (MDT) database. Endoscopy, histology and clinic letters were reviewed from the Electronic Patient Record. Information collected included patient demographics, polyp histology, the degree of cancer differentiation and invasion, whether surveillance or surgery was utilised, the rate of residual malignancy identified within surgical specimens and 1 year mortality.The aim was to determine the management and outcome of patients with malignant polyps in our institution over a 3 year period (2010–13). Results: Our institution is in a district hospital which serves a population of 500, 000 in North London. Twenty patients were identified (M = 12; mean age 60 yrs; range 53–80 yrs). Estimated polyp size ranged from 3 mm to 20 mm [pedunculated = 9 (45%); sessile = 11 (65%)]. All polyps were adenocarcinomas [well differentiated = 1 (5%); moderately differentiated = 15 (75%); poorly differentiated = 1 (5%); highly suspicious of malignancy, but managed as malignant polyps = 3 (15%)]. Lymphovascular invasion was present in only 1 case (5%). Resection margins were clear in 9 patients (45%), positive in 4 (20%) and indeterminate in 7 (35%). Ten patients (50%) underwent surgery: 5 (50%) had a laparoscopic anterior resection, 3 (30%) had a laparoscopic hemicolectomy and 2 (20%) had Transanal Endoscopic MicroSurgery (TEMS). The surgical resection specimens failed to identify any residual malignancy on histology in 7 cases (70%). Two patients (10%) died of unrelated causes over a 12 month follow-up (surgical management = 1, endoscopic management =1). Conclusion: In our unit, half of all patients with a malignant polyp had subsequent surgery with its associated risks. However 70% of those patients had no residual microscopic malignancy in the resected specimen. We feel that these patients would be best served in a dedicated 'Polyp MDT' where the colonoscopist contributes to the discussion. Experienced endoscopists can be confident about the completeness of resection even in the presence of histological uncertainty, thereby avoiding unnecessary surgery. All patients in the colonoscopy surveillance pathway have been free of cancer recurrence during the period of follow-up. Reference: 1 Williams JG, et al. Management of the malignant colorectal polyp: ACPGBI position statement. Colorectal Disease 15.s2 (2013): 1–38. Disclosure of Interest: None Declared